The Effect of Seawater and Sea Sand Composition Ratio on the Characterization of Voltage and Electric Current - Riztamala Diana; Daya Wulandari; Putri Afifa Nur Oktadina; Roviu Darojat (Unversitas Muhammadiyah Mataram, 2026)
The limited availability of fossil fuels and their environmental impacts have encouraged the development of more environmentally friendly alternative energy sources. One of the methods of renewable energy is to utilize seawater and sea sand. This research aims to analyze seawater and sea sand in generating electrical energy. Source of seawater and sea sand from Tongachi Beach Bangka Belitung Indonesia. The research method was mixing seawater and sea sand with a ratio of 100:0%, 70:30%, 50:50%, 30:70%, dan 0:100%. Measure the seawater according to the percentage 100%, 70%, 50%, 30% and 0%. Then Weigh the sea sand according to the percentage ratio 0%, 30%, 50%, 70% and 100%. Add the seawater and sea sand to the mixing container according to the weighed ratio. The electrical energy generated is determined by observing the current flow and power are seen on the multimeter. The results showed that the composition ratio of 100:0 % seawater and sea with a voltage of 0.67 V, an electrical current of 0.2 mA and a power of 0.134 watts. It has of the analysis of the composition of seawater and sea sand can potentially be used as a source of electrical energy.